HUBUNGAN POST POWER SYNDROME DENGAN TINGKAT KECEMASAN PADA NASABAH YANG PENSIUN DI ¬¬¬BANK BTPN MITRA LAYANAN TASPEN SOLOK SUMATERA BARAT PADA TAHUN 2018 - Zulkarnain Edward; Yusmahenry Galindra (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Retirement occurs when someone starts a new life. Some people face retirement with a positive outlook and there are also negative views that will cause bad things in the form of physical symptoms, emotional or including social conditions that will cause post power syndrome. For retirees who drag on Post power syndrome, they will experience anxiety and shock that is so heavy. This research is a quantitative type with an analytic research design with a cross-sectional approach. The population of this research is 94 individuals who are in retirement. The technique used is quota sampling where the sample has certain characteristics to the desired amount. Data obtained by filling out the questionnaire. The data obtained were processed statistically with SPSS using Fisher's exact test. Based on statistical test results, it was found that Ho was rejected, where there was a significant relationship between post power syndrome and the level of anxiety of customers who retired at Bank BTPN Mitra Taspen Solok, West Sumatra in 2018 with p-value = 0.001. From the results of the study it can be concluded that there is a relationship between post power syndrome and the level of anxiety in customers who retire at the Bank of BTPN Mitra Taspen Solok, West Sumatra in 2018.